Supply Chain Optimization Footwear Products in West Java to Improve Industrial Competitiveness - Hendi Iskandar (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The footwear industry in West Java is one of the largest contributors to national manufacturing exports, yet it faces persistent challenges related to supply chain inefficiency, distribution costs, and competitive vulnerability. This study proposes a quantitative supply chain optimization framework for large-scale footwear manufacturers in West Java using Linear Programming (LP) and Economic Order Quantity (EOQ) models. The objective function minimizes total supply chain cost, encompassing procurement, transportation, and inventory holding costs, subject to supply capacity, demand fulfillment, and budget constraints. Primary data were collected from four major production centers—Bandung, Garut, Bogor, and Purwakarta—representing six supplier nodes and four distribution hubs. The LP model yields an optimal distribution plan that reduces total logistics cost by 18.4% compared to the existing plan, from Rp 4,320,000,000 to Rp 3,524,160,000 per year. EOQ analysis indicates an optimal order quantity of 15,625 pairs per order cycle, reducing inventory carrying cost by 22.7%. The results confirm that the proposed optimization approach significantly improves supply chain efficiency and enhances the competitiveness of West Java's footwear industry in both domestic and global markets